Modeling a graph data model for FHIR resources - Kruse, Henner M; Helhorn, Alexander; Phan-Vogtmann, Lo An; Thomas, Eric; Heidel, Andrew J; Saleh, Kutaiba; Scherag, André; Ammon, Danny (2019)
Introduction: (Fast Healthcare Interoperability Resources) is a modern standard for communication and representation of clinical data, where each dataset is defined by a single resource, linked to other resources [ref:1]. But FHIR® does explicitely not define how to persist these resources[for full text, please go to the a.m. URL]